Adventures in Aidland : the anthropology of professionals in international development - Mosse, David (Studies in public and applied anthropology ;, 2011)
Anthropological interest in new subjects of research and contemporary knowledge practices has turned ethnographic attention to a wide ranging variety of professional fields. Among these the encounter with international development has perhaps been longer and more intimate than any of the others. Anthropologists have drawn critical attention to the interfaces and social effects of development's discursive regimes but, oddly enough, have paid scant attention to knowledge producers themselves, despite anthropologists being among them. This is the focus of this volume. It concerns the construction and transmission of knowledge about global poverty and its reduction but is equally interested in the social life of development professionals, in the capacity of ideas to mediate relationships, in networks of experts and communities of aid workers, and in the dilemmas of maintaining professional identities.